Regional Divisions of India A Cartographic Analysis, Vol-X, Series-1 - Shashidhar, H. (Karnataka, 1991)
Regional Divisions of Districts,Belgaum, Bidar, Bjapur, Gulbarga, Bellary, Chikmagalur, Chitradurga, Dharwad, Raichur, Shimoga, Bangalore, Bangalore Rural, Hassan.
Keywords: Occasional Papers; Regional Divisions of India A Cartographic Analysis